PAH Atmospheric Deposition in High Mountain Lakes - Arellano, Lourdes; Fernández, Pilar; Camarero, Lluís; Catalan, Jordi; Grimalt, Joan O. (European Geosciences Union, 2018)
Polycyclic aromatic hydrocarbons (PAHs) were analyzed in bulk atmospheric deposition samples collected at four European high mountain areas, Gossenköllesee (Tyrolean Alps), Redon (Central Pyrenees), Skalnate Pleso (High Tatra Mountains) and Lochnagar (Grampian Mountains) between 2004 and 2006. Sample collection was performed monthly in the first three sites and biweekly in Lochnagar. The number of sites, period of study and sampling frequency provide the most comprehensive description of PAH fallout in high mountain areas addressed so far. The average PAH deposition fluxes in Gossenköllesee, Redon and Lochnagar ranged between 0.8–2.1µgm−2mo−1, and in Skalnate Pleso it was 9.7µgm−2mo−1, showing the influence of substantial inputs from regional emission sources. The deposited distributions of PAH were dominated by parent phenanthrene, fluoranthene and pyrene, representing 32–60% of total. The proportion of phenanthrene, the most abundant compound, was higher at the sites of lower temperature, Gossenköllesee and Skalnate Pleso, showing higher transfer from gas phase to particles of the more volatile PAHs. The sites with lower insolation, e.g. those located at lower altitude, were those with higher proportion of photooxidable compounds such as benz[a]anthracene. According to the data analysed, precipitation is the main driver of PAH fallout. However, when rain and snow deposition were low, particle settling also constitutes an efficient driver for PAH deposition. Redon and Lochnagar were the two sites receiving highest rain and snow and the fallout of PAH fluxes was related to this precipitation. No significant association was observed between long-range backward air trajectories and PAH deposition in Lochnagar, but in Redon PAH fallout at higher precipitation was essentially related with air masses originating from the North Atlantic, which were dominant between November and May (cold season). In these cases, particle normalized PAH fallout was also associated to higher precipitation as these air masses were concurrent with lower temperatures, which enhanced gas to particle partitioning transfer. In the warm season (June–October), most of the air masses arriving to Redon originated from the south and particle deposition was enhanced as consequence of Saharan inputs. In these cases, particle settling was also a driver of PAH deposition despite the low overall PAH content of the Saharan particles. In Gossenköllesee, the site receiving lowest precipitation, PAH fallout was also related to particle deposition. The particle normalized PAH fluxes were significantly negatively correlated to temperature, e.g. for air masses originating from Central/Eastern Europe, showing a dominant transfer from gas phase to particles at lower temperatures, which enhanced PAH fallout, mainly of the most volatile hydrocarbons. Comparison of PAH atmospheric deposition and lacustrine sedimentary fluxes showed much higher values in the latter case, 24–100µgm−2yr−1 vs. 120–3000µgm−2yr−1, respectively. A strong significant correlation was observed between these two fluxes which is consistent with a dominant origin related with atmospheric deposition at each site.